Efectiveness of piled strip raft foundation as an alternative design of pile to set foundation on thick soft clay - Puspanthan Subramaniam, 1985-; Khairul Anuar Kassim; Fakulti Kejuruteraan Awam (2012)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2012